Rancang Bangun Alat Penanganan Dan Pengendalian Kebakaran Berbasis Arduino Nano Dengan Si stem IoT - Laksmana, Bisma (Teknologi Rekayasa Jaringan Telekomunikasi, 2021)
This will be very useful for residents of the house to prevent what can cause a fire incident. In the main research, system design will make a fire detector and smoke and gas detector, using 3 Flame Sensors and 3 MQ-2 Sensors. This design concept will be installed in each room which consists of 3 rooms. The microcontroller used in this design system is an Arduino Nano microcontroller which functions as part of the Flame Sensor controller, MQ-2 Sensor, WeMos D1 Mini, Relay, and Buzzer. Furthermore, the system output uses a Flame Sensor which is already in a HIGH state so that it can activate automatic shutdown, and the tool can submit a notification to the occupants of the house via an android application called Blynk and an alarm sounds. If the implementation of the MQ-2 Sensor is in a HIGH state, the system will provide warning instructions in the form of a notification from the android and an alarm will sound for the occupants of the house. So that the residents of the house will be prepared to take action to extinguish the fire in the house. Keywords : Fire, Flame Sensor, MQ-2 Sensor